PENGARUH TINGKAT SUKU BUNGA, IHK, PDB REAL ESTATE TERHADAP HARGA PROPERTI DI INDONESIA PERIODE TAHUN 2010-2016 - METHA ADEYATNI (PPJP Universitas Lambung Mangkurat, 2018)
This research unducted to (1) analyze the influence of interest rate, consumer price index, gross domestic product of real estate in Indonesia; (2) to know the most dominant factor that influencing property price in Indonesia at 2010-2016. The Scope of this research is Indonesia as the research area. The data sources of this research come from secondary data that will proussing using multiple regression analysis by F-test (simultaneously) and T-tes (Partially). The research’s result proves that simultaneously gross domestic bruto of real estate is influencing property price. And partially proves of real estate and consumer price index are influencing property price significantly.Keywords:Interest Rate, Counsume Price Index, Gross Domestic Bruto of Real Estate, and Property Price.